Optimizing mycelial growth of Trametes versicolor HBB 7328 for enzyme production and green energy - Nikita Goyat; Rajeev Kumar Kapoor; Baljeet Singh Saharan; Prexha Kapoor; Deepika Dhanda (Academia Green Energy)
Trametes versicolor, a common upper polyporus fungus, demonstrates mycelial growth that is influenced by temperature, pH, and media composition. This study aimed to optimize these conditions, as well as carbon and nitrogen sources, to enhance the mycelial growth of the white-rot fungus T. versicolor HBB 7328. This fungus shows significant potential for green energy applications due to its enzymatic activities. The research found that the fungus achieved maximal mycelial growth at 30°C (8.24 mm/day) and pH 7 (6.34 mm/day). Among various carbon sources, maltose resulted in the highest growth rate of 10.62 mm/day, whereas malt extract proved to be the most effective nitrogen source, supporting a growth rate of 8.96 mm/day. Enzymatic activity screening showed that T. versicolor HBB 7328 was positive for laccase, cellulase, protease, and xylanase activities. Notably, it exhibited substantial laccase activity (50.167 U/mL). These results are pivotal for developing pure cultures and conducting further studies on the enzymatic activities of T. versicolor HBB 7328. The high laccase activity, in particular, underscores its potential in biotechnological applications such as pollutant biodegradation and biofuel production, advancing green energy solutions.